Accountability of PBB-P2 Recording and Financial Information Quality in Supporting SDG-Based Sustainable Village Development (A Qualitative Study in Petudua Village, Kolaka Regency) - Hasmawati Timpa; Iien Rohmatun Nisa; Muh. Sukran S.; Surianto Ilham; Sriayu Pracita (CV Edujavare Publishing, 2026)
This study analyzes the accountability of PBB-P2 recording and the quality of financial information as part of sustainable village development based on the Sustainable Development Goals (SDGs). The study uses a descriptive qualitative approach with a case study in Petudua Village, Tanggetada District, Kolaka Regency. Data were derived from observation, discussion, data-recording simulations, activity evaluation, and documentation involving 49 participants. The analysis focuses on taxpayer and tax-object data, revenue recording, transaction traceability, reporting, community understanding, and their relationship with financial accountability. The findings indicate that the quality of PBB-P2 recording is inseparable from the quality of taxpayer and tax-object data, administrative accuracy, staff capacity, and community understanding. Strengthening these processes can improve the reliability of financial information and reinforce accountability mechanisms. From an SDGs perspective, the strongest alignment is with SDG 16 on effective, accountable and transparent institutions and SDG 17 on domestic resource mobilization and partnerships. This study contributes an accounting perspective by positioning PBB-P2 not merely as a tax-collection issue but as a public transaction requiring documentation, recording, internal control, and accountable financial information. Because time-series revenue data, target-realization ratios, and arrears data were unavailable, the study does not claim a quantitative increase in revenue.